Pengelolaan Dana Zakat, Infak dan Sedekah (ZIS) dalam Peningkatan Ekonomi Mustahik Pada BAZNAS Provinsi Bengkulu - Rista Putriana Putriana; Eka Sri Wahyuni; Nonie Afrianty (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
ZIS funds are potential funds that can be used to build community welfare in the form of revolving (productive) funds. Management of ZIS funds is carried out through the Bengkulu Province National Zakat Agency (BAZNAS). It is known that the management of ZIS funds must reach a distribution stage that is productive, empowering and seeks to optimize the potential of mustahik. Distribution of ZIS funds can be carried out through various forms of providing business capital and business equipment to mustahik. BAZNAS issued regulations regarding zakat management through the Republic of Indonesia National Zakat Amil Agency Regulation Number 4 of 2018 concerning Reporting on the Implementation of Zakat Management. The research method used is a descriptive analytical method with a qualitative approach. The results of this research show that: 1) The ZIS fund collection system by BAZNAS Bengkulu Province is carried out using social media and payment of ZIS funds is carried out using an inter-bank transfer system and directly. 2) The distribution of ZIS BAZNAS funds in Bengkulu Province is carried out productively through business program capital (3) Standard monitoring of ZIS funds is carried out by means of a sharia audit which is a report every 6 months. From the results of research by interviewing ten mustahik people, it was found that productive management of ZIS funds can increase mustahik income before and after receiving ZIS fund assistance.